A STRONG SECURITY PROTOCOL AGAINST FINGERPRINT DATABASE ATTACKS - U, Latha; K, Ramesh Kumar (ICTACT journal on image and video processing, 2013)
The Biometric data is subject to on-going changes and create a crucial problem in fingerprint database. To deal with this, a security protocol is proposed to protect the finger prints information from the prohibited users. Here, a security protocol is proposed to protect the finger prints information. The proposed system comprised of three phases namely, fingerprint reconstruction, feature extraction and development of trigon based security protocol. In fingerprint reconstruction, the different crack variance level finger prints images are reconstructed by the M-band Dual Tree Complex Wavelet Transform (DTCWT). After that features are extracted by binarization. A set of finger print images are utilized to evaluate the performance of security protocol and the result from this process guarantees the healthiness of the proposed trigon based security protocol. The implementation results show the effectiveness of proposed trigon based security protocol in protecting the finger print information and the achieved improvement in image reconstruction and the security process.